2015
DOI: 10.1371/journal.ppat.1005155
|View full text |Cite|
|
Sign up to set email alerts
|

The NLRP3 Inflammasome and IL-1β Accelerate Immunologically Mediated Pathology in Experimental Viral Fulminant Hepatitis

Abstract: Viral fulminant hepatitis (FH) is a severe disease with high mortality resulting from excessive inflammation in the infected liver. Clinical interventions have been inefficient due to the lack of knowledge for inflammatory pathogenesis in the virus-infected liver. We show that wild-type mice infected with murine hepatitis virus strain-3 (MHV-3), a model for viral FH, manifest with severe disease and high mortality in association with a significant elevation in IL-1β expression in the serum and liver. Whereas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 49 publications
3
52
0
Order By: Relevance
“…Previous studies suggested fgl2 played a vital role in this process with a 15-40% increase of survival when fgl2 was deleted (12,15,27,28). Multiple inflammatory factors or mediators including TNF-α and IFN-γ, IL-1β and C5aR have been demonstrated to promote FH progression with significant discrepancies between liver damage and survival rate (29)(30)(31)(32), which is accordant with our observation that CC10 substantially alleviated liver injury though survival rate improved mildly. The survival rate based on hours may be more accurate to examine the effect of CC10 on FH.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies suggested fgl2 played a vital role in this process with a 15-40% increase of survival when fgl2 was deleted (12,15,27,28). Multiple inflammatory factors or mediators including TNF-α and IFN-γ, IL-1β and C5aR have been demonstrated to promote FH progression with significant discrepancies between liver damage and survival rate (29)(30)(31)(32), which is accordant with our observation that CC10 substantially alleviated liver injury though survival rate improved mildly. The survival rate based on hours may be more accurate to examine the effect of CC10 on FH.…”
Section: Discussionsupporting
confidence: 90%
“…Blocking of IL-17A or IL-1 resulted to be potential targets for therapeutic treatment of viral exacerbations of chronic lung inflammation [219]. Authors described that inflammasome complex/IL-1β are an essential signaling pathway, which is over activated and directly causes the severe liver disease during viral infection [220]. Anakinra (ANK), a human IL-1R antagonist, has been approved for the treatment of RA, AOSD, and other severe autoimmune and autoinflammatory disorders including tumor necrosis factor receptor-associated periodic syndrome (TRAPS) [221].…”
Section: Anti-interleukinmentioning
confidence: 99%
“…Inflammasomes are also the molecules responsible for induction of inflammation in the liver following injection of alum [53]. NLRP3 inflammasome and its signaling molecules also significantly participate in the induction of fulminant hepatitis by MHV [54]. However, studies regarding HCV and HBV revealed the induction of chronic hepatitis by inflammasomes and their related molecules, including ASC, caspase-1, IL-1β, and IL-18 [55][56][57].…”
Section: Inflammasomes; the Crucial Inducers Of Chronic Inflammationmentioning
confidence: 99%